Passive Voice Transformation (e-Journal of Linguistics, 2019)
It is well known that the differences between the languages and the different levels ofrelationship between them and the use of the English passive voice in Albanian language arecomplex achievements of hypotheses given by language thinkers, because the language first ofall is a process and processes change from time to time as a result of new language achievementsand transformations and as a result of changes in people's worldview.The English and Albanian passive voice do not have a single grammatical structure and that thisshould be related to numerous legalities that follow the languages in their internal and externaldevelopment. The studies carried out in terms of linguistic features, even of the passive voiceaccording to the comparative method, have opened new paths to see similarities and differenceseven in the passive voice structure.This study is intended to give our modest contribution to notice the similarities and differences inthe use of the passive voice as well as its structure in both languages. This contrastive analysistries to facilitate the acquisition of English as a foreign language for students, pupils, to make thetranslation from English into Albanian and vice versa easier, to provide linguistic information tolanguage researchers. The comparison is supported by the following English novels and theirtranslated versions in Albanian such as: “Oliver Twist” by Charles Dickens and translated bySkënder Luarasi and “Silas Marner” by George Eliot and translated by Ramazan Hysa, wheresimilar as well as different features have been found.
Keywords: passive voice; active voice; verb; transformation; object